Control interno de la Sociedad Schuldt Vizuete del cantón Babahoyo, período 2022. - Collantes Falvy, Spencer Galilei (2024)
Internal control is an essential part of the effective operation of any company. It consists of a set of processes, policies and procedures designed to ensure that a company effectively achieves its objectives, complies with laws and regulations, protects its assets and maintains the integrity of its operations. Additionally, it plays a critical role in financial provisioning and management, reduces errors and improves resource allocation to achieve business objectives. However, operational and financial risks may arise if an effective control environment is not established or the necessary assessments are not carried out. This problem is evident in the case of the Schuldt Vizuete Society of the city of Babahoyo, province of Los Ríos, Ecuador. In this organization, the lack of effective controls and audits in the warehouse department created significant obstacles to production operations. Highlights key internal issues related to internal control and inventory management. The main objective of this case study is to evaluate the internal controls of the Schuldt Vizuete Company in the period 2022. It focuses on identifying control risks in the warehouse department and internal weaknesses that affect inventory management. The study includes financial, administrative, tax and control management, with special focus on the audit and internal control subfields. Through this study, the aim is to provide recommendations based on standardized internal control methods to optimize the efficiency and financial situation of the organization.